Design and Construction of Cassava Grating Machine Using 220 V Electric Motor Voltage - Rizki Tri Ramdani; Amir; Karyadi (YCMM, 2024)
Cassava shredding machine has become an integral part of the modern food industry, facilitating the process of grating cassava quickly and efficiently. In this context, this study describes the design of a cassava grater machine that adopts a 220 V electric motor voltage as the main power source. In the design of this machine, the electric motor voltage of 220 V was selected with careful consideration of efficiency and performance. This report describes the main components of the machine, including the electric motor, special grater blades, frame and safety mechanism. Also described is the process of grating cassava which occurs through the rotation of an electric motor, giving smooth and consistent grating results. The advantages of using a 220 V electric motor voltage are revealed in this article, focusing on greater power and power stability. In the context of the food industry, these machines have the potential to increase the productivity and quality of the final product. This research contributes to further understanding of the utilization of 220 V electric motor voltage in the design of a cassava grater machine. Its potential implications in increasing the efficiency and effectiveness of the grating process and its impact in the food industry make this research relevant and valuable in the development of future food technology.